NONSTEROIDAL TOPICAL MEDICATION IN THE THERAPY OF ATOPIC DERMATITIS IN CHILDREN - L. S. Namazova-Baranova; E. A. Vishneva; R. M. Torshkhoeva; Z. N. Dzagoeva; A. A. Alekseeva; J. G. Levina; K. E. Efendieva; N. I. Voznesenskaya; L. K. Aslamazyan (Union of pediatricians of Russia, 2012)
Article is devoted to atopic dermatitis (AD) in children. The high prevalence of this pathology and significant social and economic burden are responsible for the relevance of search for new medications for the treatment of AD, which will accelerate the achievement of remission. Inclusion of emollient in basic therapy for patients with atopic dermatitis of any severity is necessary element of improvement treatment efficacy, shorten duration of steroid consumption, lengthen the period of remission and reduce the number of exacerbations.